Branched-chain amino acids supplementation enhances exercise capacity and lipid oxidation during endurance exercise after muscle glycogen depletion - Gualano, A. B.; Bozza, T.; Lopes De Campos, P.; Roschel, H.; dos Santos Costa, A.; Luiz Marquezi, M.; Benatti, F.; Herbert Lancha Junior, A. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: It has been demonstrated that branched-chain amino acids (BCAA) transaminase activation occurs simultaneously with exercise-induced muscle glycogen reduction, suggesting that BCAA supplementation might play an energetic role in this condition. This study aimed to test whether BCAA supplementation enhances exercise capacity and lipid oxidation in glycogen-depleted subjects. METHODS: Using a double-blind cross-over design, volunteers (N.=7) were randomly assigned to either the BCAA (300 mg . kg . day -1) or the placebo (maltodextrine) for 3 days. On the second day, subjects were submitted to an exercise-induced glycogen depletion protocol. They then performed an exhaustive exercise test on the third day, after which time to exhaustion, respiratory exchange ratio (RER), plasma glucose, free fatty acids (FFA), blood ketones and lactate were determined. BCAA supplementation promoted a greater resistance to fatigue when compared to the placebo (+17.2%). Moreover, subjects supplemented with BCAA showed reduced RER and higher plasma glucose levels during the exhaustive exercise test. CONCLUSION: In conclusion, BCAA supplementation increases resistance to fatigue and enhances lipid oxidation during exercise in glycogen-depleted subjects.